2017
DOI: 10.1002/mc.22659
|View full text |Cite
|
Sign up to set email alerts
|

Potentially functional variants in lncRNAs are associated with breast cancer risk in a Chinese population

Abstract: Long non-coding RNAs (lncRNAs) participate in the development of breast cancer. Genetic variants in lncRNAs may be involved in their abnormal expressions and associated with cancer risk. In the present study, we performed RNA sequencing on five paired breast cancer tumor and adjacent non-cancerous tissues to obtain differentially expressed lncRNAs. We systematically selected potential regulatory variants of these lncRNAs and investigated the associations between these variants and breast cancer susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Further study has suggested that the plasma HOTAIR level is positively associated with lymph node metastasis and estrogen receptor, and reduced after surgery in BC patients [118]. Genetic polymorphisms of HOTAIR are associated with BC risk in different races [119,120,121]. The latest findings suggest that HOTAIR-containing exosomes could be detected in BC patients’ blood [122,123].…”
Section: Lncrnas In Breast Cancer (Bc)mentioning
confidence: 99%
“…Further study has suggested that the plasma HOTAIR level is positively associated with lymph node metastasis and estrogen receptor, and reduced after surgery in BC patients [118]. Genetic polymorphisms of HOTAIR are associated with BC risk in different races [119,120,121]. The latest findings suggest that HOTAIR-containing exosomes could be detected in BC patients’ blood [122,123].…”
Section: Lncrnas In Breast Cancer (Bc)mentioning
confidence: 99%
“…Although the treatment of breast cancer has made great progress and the mortality rate has decreased year by year, due to the high incidence of tumor specific death, the prognosis of patients is still worthy of attention 2,3 . There are about 1.7 million new cases every year in the world, accounting for 25% of all new cancer cases among women 4 . According to the data from the Centers for Disease Control and Prevention (CDC) 5 , 245,299 new breast cancer cases occurred in the United States in 2016, and 41,487 women died of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the regulatory network underlying BC is an essential focus point for future studies. There is an increasing amount of evidence that long non-coding RNAs (lncRNAs) participate in the development and progression of BC and potentially serve as markers of diagnosis or prognosis (4,5).…”
Section: Introductionmentioning
confidence: 99%